Dual band printed patch antenna on ceramic–polytetrafluoroethylene composite material substrate for GPS and WLAN applications - Ahsan, M.R.; Islam, M.T.; Ullah, M.H.; Mansor, M.F.; Misran, N. (Kluwer (now part of Springer), 2016)
In this paper, a design concept of modified rectangular shape slotted patch antenna with microstrip feed is proposed for GPS and WLAN applications. The proposed simple planar design of the planar antenna is composed of partially extended radiating surface which is loaded with L-shape slot and two wide square slots. The optimized design of the antenna has overall dimension of 40×40mm2 and is fabricated on 1.905 mm thick high dielectric substrate (εr= 10.2) of high frequency copper laminated ceramic composite substrate. The antenna design, simulation and parametric analysis have been performed on finite element method based full-wave 3D electromagnetic field simulation software. The experimental results show that the fabricated antenna has achieved impedance bandwidths (S11 ≤ - 10 dB) of around 780 MHz (1.13–1.91 GHz) at resonant frequency of 1.48 GHz and 1220 MHz (4.83–6.05 GHz) at resonant frequency of 5.61 GHz respectively. The gain of the fabricated antenna gives maximum value of 3.42 and 4.37 dBi for lower and upper frequency band of operations respectively. The proposed antenna shows almost consistent radiation patterns with adequate radiation efficiency over the frequency bands which make the antenna appropriate for providing services in both L1/L2 GPS and 5.2/5.8 GHz WLAN bands.